P325 Upper gastrointestinal haemorrhages and COVID-19: a nationwide cohort study of the pandemic's impact on hospitalisations. (19th June 2022) - Robert-Montaner, Ïa; Crooks, Colin
Abstract : Background: Upper gastrointestinal bleed (UGIB) is the most common acute medical emergency seen by gastroenterologists in the UK. Methods: A population-based nationwide data analysis was carried out using Hospital Episode Statistics data and Office for National Statistics data from March 2012 to March 2021. Data from 2021 has been merged with 2020 data, hence will be referred to as 2020 data. Patients in England with ICD-10 codes relating to UGIB were included. Statistical management and analysis were carried out with RStudio software. Rates were calculated and Poisson Distribution Model was used to calculate 95% Confidence Intervals (CI). Hospitalisations and trends in each year were stratified by age and gender. Incidence rate ratios of UGIB hospitalization were adjusted for age, gender and year using the Poisson Regression Model. Results: All 4 subgroups analysed (melena, haematemesis, ulcer and variceal) portrayed different trends from 2012 to 2019, but total codes decreased by 19% from 2019 to 2020. While variceal codes had the lowest percentage decrease, 12.1% from 2019 to 2020, ulcer codes had the highest percentage decrease, 22.2% from 2019 to 2020. Overall, males presented with up to 1.8 times higher hospitalisation rates than females. In melena, haematemesis and ulcer subgroups 65+ age group had the highest rates throughout the 9-year study period, with rates per 100, 000 of 403.43 (95% CI: 402.11, 404.76), 354.68 (353.44, 355.93), and 153.07 (152.26, 153.89) respectively. After adjusting for confounders (age, gender, and years), the trends previously described did not change. Hence, these covariates did not impact the decline in UGIB hospital admissions observed from 2019 to 2020. Conclusion: To our knowledge, this is the first nation-wide cohort study to analyse UGIB hospital admission throughout the COVID-19 pandemic. We hypothesise that the decrease in UGIB hospitalisations is associated with a decrease in endoscopic procedures performed as well as an increase in fear of being hospitalised. However, since UGIB is an acute presentation and no risk factors decreased to this extent during the pandemic, we predict that hospital admissions decreased but not overall UGIB presentation rates. Therefore, as stated in previous literature, we anticipate a rebound period where UGIB presentations will increase as previously minor bleeds will likely require urgent medical attention.